2012
DOI: 10.3390/en5104186
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic Trough Photovoltaic/Thermal Collectors: Design and Simulation Model

Abstract: This paper presents a design procedure and a simulation model of a novel concentrating PVT collector. The layout of the PVT system under investigation was derived from a prototype recently presented in literature and commercially available. The prototype consisted in a parabolic trough concentrator and a linear triangular receiver. In that prototype, the bottom surfaces of the receiver are equipped with mono-crystalline silicon cells whereas the top surface is covered by an absorbing surface. The aperture area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…The study presented herein is based on the work previously reported by Yang et al [1], and references [2][3][4][5][6][7][8][9][10][11][12][13][14] where a flat plate solar collector is attached to a PV panel. The hybrid system in question is composed of the PV solar panel and thermal solar tube collector as well as a heat pump as shown in Figure 1.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The study presented herein is based on the work previously reported by Yang et al [1], and references [2][3][4][5][6][7][8][9][10][11][12][13][14] where a flat plate solar collector is attached to a PV panel. The hybrid system in question is composed of the PV solar panel and thermal solar tube collector as well as a heat pump as shown in Figure 1.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Calise and Vanoli [235] studied how varying the length of their proposed CPVT system affects performance. They found that both electrical and thermal efficiencies slightly decrease (o1%) for a length increase from 4 to 16 m. This is attributed to the increased cell temperature and the accompanying increased thermal losses.…”
Section: System Sizing and Bop Componentsmentioning
confidence: 99%
“…In particular, new TRNSYS types have been created for the CPVT and the MED. The model of the CPVT was recently presented in literature [33], whereas the MED model is described in detail in Ref. [13].…”
Section: Simulation Modelmentioning
confidence: 99%